# 5(3m-2)-9(5-2m)=4m+2(5m+1)

## Simple and best practice solution for 5(3m-2)-9(5-2m)=4m+2(5m+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 5(3m-2)-9(5-2m)=4m+2(5m+1) equation:

5(3m-2)-9(5-2m)=4m+2(5m+1)
We move all terms to the left:
5(3m-2)-9(5-2m)-(4m+2(5m+1))=0
We add all the numbers together, and all the variables
5(3m-2)-9(-2m+5)-(4m+2(5m+1))=0
We multiply parentheses
15m+18m-(4m+2(5m+1))-10-45=0

We calculate terms in parentheses: -(4m+2(5m+1)), so:
4m+2(5m+1)
We multiply parentheses
4m+10m+2
We add all the numbers together, and all the variables
14m+2
Back to the equation:
-(14m+2)

We add all the numbers together, and all the variables
33m-(14m+2)-55=0
We get rid of parentheses
33m-14m-2-55=0
We add all the numbers together, and all the variables
19m-57=0
We move all terms containing m to the left, all other terms to the right
19m=57
m=57/19
m=3

`